Prorrogação antecipada dos contratos de concessão de serviço público - Picolo, Felipe Miranda Ferrari (2023)
The objective of this study is to investigate and analyze the issue of early extensions of concession agreements of public service. The execution of the concession agreements signed in the 90s, the emergence of new needs arising from public policies and the adequate provision of public services gave rise to legislative, scholar and case law discussions on the possibility of extending the concession agreements, in period considerably earlier than its original term, to include new obligations to the concessionaire. The concept of early extension appears in the federal law of the port sector, spreading to different public services and in normative acts issued by other entities of the Federation, each with its own particularity. With the application of this institute, higher courts and oversighting authorities were provoked to render decisions on the constitutionality and legality of the early extensions, in abstract and specific cases. It is based on this collection (legislative and case law) that the dissertation was produced and organized into its 6 chapters. The legal regime of early extension differs from the modalities of extraordinary extension of concession agreements of public service (extension for economicfinancial rebalancing and extension for the continuity of the public service provision) and is close to the ordinary extension. The main element that separates the early extension from the ordinary extension is the time factor, so that the production of the effects of the extension occurs at a moment relatively before the end of the concession period. Based on normative acts and on precedents, we extract five requirements that must be observed to authorize the early extension: the concession must have been preceded by a public bidding process; there must be an express provision in the agreement or in a bidding notice authorizing the contractual extension; the agreement must be in force and the request for early extension must be presented timely; the Government must demonstrate the compatibility of the early extension with the public interest; and the social participation must be ensured. Finally, the study identifies the main counterparties included in the concession agreements as a result of the early extension: the inclusion of new investment obligations; payment of the grant for the extension; cross investments; tariff reduction; and contractual suitability to ensure the provision of adequate public service to users